A Systematic Review of Within-Population Variation in the Size of Home Range Across Ungulates: What Do We Know After 50 Years of Telemetry Studies? - Seigle-Ferrand, Juliette; Atmeh, Kamal; Gaillard, Jean-Michel; Ronget, Victor; Morellet, Nicolas; Garel, Mathieu; Loison, Anne; Yannic, Glenn (Frontiers in Ecology and Evolution, 2021)
Studying the factors determining the sizes of home ranges, based on body mass, feeding style, and sociality level, is a long-standing goal at the intersection of ecology and evolution. Yet, how species-specific life history traits interact with different components of the landscape to shape differences in individual home ranges at the within-population level has received much less attention. Here, we review the empirical literature on ungulates to map our knowledge of the relative roles of the key environmental drivers (resource availability, landscape heterogeneity, lethal and non-lethal risks) of the sizes of individual home ranges within a population, and assess whether species’ characteristics (body mass, diet and social structure), account for observed variation in the responses of the sizes of individual home ranges to local environmental drivers. Estimating the sizes of home ranges and measuring environmental variables raise a number of methodological issues, which complicate the comparison of empirical studies. Still, from an ecological point of view, we showed that (1) a majority of papers (75%) supported the habitat productivity hypothesis, (2) the support for the influence of landscape heterogeneity was less pervasive across studies, (3) the response of cattle-type to variation in food availability was stronger than the response of moose-type, and (4) species-specific body mass or sociality level had no detectable effect on the level of support to the biological hypotheses. To our surprise, our systematic review revealed a dearth of studies focusing on the ecological drivers of the variation in the sizes of individual home ranges (only about 1% of articles that dealt with home ranges), especially in the later decade where more focus has been devoted to movement. We encourage researchers to continue providing such results with sufficient sample sizes and robust methodologies, as we still need to fully understand the link between environmental drivers and individual space use while accounting for life-history constraints.